THE SOUTH AFRICAN LAW ON "PRODUCTS LIABILITY" - QUO VADIS? - Basson, Johann (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: Historically the term "products liability" has been confined to the law of delict, and is defined as the liability that arises when a product contains a defect which leads to damage such as to property (patrimonial loss), the death of a person, bodily harm, pain and suffering, shock, discomfort, deformity, loss of amenities or shortened life expectation. It is the author’s view that the term "products liability" becomes a misnomer if limited to the law of delict. The author propagates the idea that "products liability" must mean liability arising when a person renders a product unsafe together with a reasonable foreseeable risk of another person(s) being exposed to the unsafe product under circumstances where reasonable precautions could have been taken to prevent it. Such liability arises irrespective as to whether such product actually causes damage, harm or death, and irrespective of whether the product is exposed to the public domain or not and irrespective as to whether the case is based on civil or criminal proceedings. Subsequently the question is investigated: "Has our law on products liability kept pace with technological, social and economic developments?" AFRIKAANSE OPSOMMING: Histories is die begrip "produkte-aanspreeklikheid" beperk tot die terrein van die deliktereg. Dit word gedefinieer as die aanspreeklikheid wat ontstaan deurdat ’n produk ’n defek bevat wat aanleiding gegee het tot skade, soos aan eiendom, die dood van ’n persoon, liggaamlike beserings, pyn en lyding, skok, ongerief, verminking, verlies aan lewensgenietinge of ’n verkorte lewensverwagting. Dit is die outeur se siening dat die begrip "produkte-aanspreeklikheid" ’n verkeerde benaming word indien beperk tot die terrein van die deliktereg. Die outeur huldig die siening dat "produkte-aanspreeklikheid" moet beteken aanspreeklikheid wat volg wanneer ’n persoon ’n produk onveilig maak tesame met ’n redelike voorsienbare risiko dat ’n ander persoon(e) aan die onveilige produk blootgestel kan word onder omstandighede waar hy redelike stappe kon geneem het om dit te voorkom. Sodanige aanspreeklikheid ontstaan ongeag of sodanige produk inderdaad skade, besering of dood veroorsaak het, ongeag of the publiek aan die produk blootgestel word al dan nie, en ongeag of die saak gebaseer is op siviele of kriminele aksies. Vervolgens word die vraag behandel: "Ret ons reg betreffende produkte-aanspreeklikheid tred gehou met tegnologiese, sosiale en ekonomiese verwikkelings?"